Demographic policy and migration processes in modern Russia - V. Kasyanov, Valery (2018)
The national security of Russia is largely determined by modern migration processes in the Russian regions. Against the background of international globalization, based on the opportunities for social, political and socio-economic development, competition and dominance, there is a visible transformation of migration processes taking place in the conditions of the development of modern Russian society. Migration processes strengthen their influence not only on the political and socio-economic situation in Russia, but also on the demographic sphere of the life of society, creating new challenges in the field of national security. The article analyzes social, economic and cultural consequences of ethnic migration in Russian society. Regional migration processes represent a dangerous trend towards the formation of Russia's national security. The authors come to the conclusion that the current migration processes in the Russian regions are the result of ambiguous, hardly predictable socio-economic, political processes and socio-cultural processes. The authors believe that a regular increase in ethnic migration threatens the national security of Russian society. Migration, as a consequence of socio-economic development, socio-political instability, on the one hand, can contribute to improving economic and social conditions, and on the other - to increase inequality, to cause a new turn of social and political intension. Understanding of this circumstance allows optimizing the demographic policy in the security system, the achievement of which is possible only with the formulation of an adequate Russian demographic policy.